Heterozygosity screening in oil palm - Wilkinson, M. J. (Malaysian Palm Oil Board, 2019)
Genetic diversity studies of oil palm (Elaeis guineensis Jacq.) at Sumatra Bioscience (SumBio) have revealed variation in the various sets of germplasm at mapped genetic loci. This variation is presented as a range of alleles that can be present at a locus and at which the heterozygosity/homozygosity at each locus can be screened. It was therefore of interest to screen germplasm at SumBio to determine the level of heterozygosity in breeding and experimental material. Simple sequence repeat (SSR) markers were used for this purpose as they are codominant, easily scored and reliable. Variation in heterozygosity was found within the elite breeding material. Heterozygosity of parental lines has clear implications for breeding as well as genetic studies. For example, it allows the identification of genetic bottlenecks in current elite material and in achieving a wide genetic base for future breeding progress.